KANDUNGAN SENYAWA FITOKIMIA DAN VITAMIN E DARI DAUN DAN BATANG BAYAM BRASIL (Alternanthera sisso) - Aryasa, Natali Allya Graciandi; Madyaningrana, Kukuh; -, Krismono (BUANA SAINS, 2024)
Brazilian spinach possesses untapped potential as an immunomodulator, containing beneficial flavonoids and vitamin E. This research aimed to explore the phytochemical and vitamin E content in Brazilian spinach leaves and stems, laying the foundation for its use as a food crop. The result showed that the leaves and stems of Brazilian spinach contain similar phytochemicals, including alkaloids, flavonoids, and tannins. Moreover, Brazilian spinach was shown to be a source of vitamin E, with Brazilian spinach leaf flour containing approximately 42.2914 mg of vitamin E per 100 grams and Brazilian spinach stem flour containing roughly 27.32095 mg of vitamin E per 100 grams.